2005
DOI: 10.1074/jbc.m405469200
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Formation of Inositol 1,4,5-Trisphosphate Receptor Requires Its Transition to Open State

Abstract: 3 -induced conformational change to the open state. We also found that GFP-IP 3 R1 clusters colocalized with ERp44, a luminal protein of endoplasmic reticulum that inhibits its channel activity. This is the first example of ligandinduced clustering of a ligand-gated channel protein.Many extracellular stimuli are received by trimeric G protein-or tyrosine kinase-coupled receptors and relayed to signaling molecules including phospholipase C (PLC), 1 which leads to production of a second messenger, inositol 1,4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 27 publications
(28 reference statements)
8
76
1
Order By: Relevance
“…As previous studies (11,13) have shown that the clustering of IP 3 R is not the result of ER redistribution, ]i measured using fura-2-loaded cells. In C and E, the cells were incubated with 2 μM ThG for 10 min in the presence (C) or absence (E) of extracellular Ca 2+ and then stimulated with 100 μM ATP.…”
Section: +mentioning
confidence: 70%
See 2 more Smart Citations
“…As previous studies (11,13) have shown that the clustering of IP 3 R is not the result of ER redistribution, ]i measured using fura-2-loaded cells. In C and E, the cells were incubated with 2 μM ThG for 10 min in the presence (C) or absence (E) of extracellular Ca 2+ and then stimulated with 100 μM ATP.…”
Section: +mentioning
confidence: 70%
“…Further studies are necessary to determine whether this theoretical model of the signaling capability is applicable to the clustering of GFP-IP 3 R3 observed in our experiments. It has been shown that ERp44, an ER luminal protein that inhibits the channel activity of IP 3 R1 (25), colocalizes with GFP-IP 3 R1 clusters induced by ATP in COS-7 cells (11). On the basis of this result, the authors suggested that ERp44 negatively regulates the channel activity of IP 3 R1 in the clusters.…”
Section: +mentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, clustering in cells is a dynamic process (5,(26)(27)(28). During this control of spiking, the positive slope of the σ-T av relation and the existence of the minimal ISI guarantee that faster spiking is also more regular despite the stochastic character of spike generation.…”
Section: Isi Distributions Depend On the Details Of Cluster Dynamicsmentioning
confidence: 99%
“…Confocal microscopy has shown that both native and tagged IP 3 Rs can form clusters. [14][15][16] But a single IP 3 R measures only ∼20 nm across, and so determining the spacings of IP 3 Rs within clusters and assessing whether IP 3 Rs are close enough to facilitate local Ca 2+ regulation lie beyond the resolution of confocal microscopy. It is generally impracticable to use patch-clamp techniques to record from ion channels within the ER, but the outer nuclear envelope is continuous with the ER membrane and amenable to patchclamp recording.…”
Section: Introductionmentioning
confidence: 99%